2017
DOI: 10.1016/j.jcin.2017.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the Safety and Feasibility of Robotically Assisted Percutaneous Coronary Intervention in Complex Coronary Lesions

Abstract: This study demonstrates the feasibility, safety, and high technical success of R-PCI for the treatment of complex coronary disease. Furthermore, comparable clinical outcomes, without an adverse effect on stent use or fluoroscopy time, were observed with R-PCI and M-PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 14 publications
3
100
1
Order By: Relevance
“…1 Glimpsing to the future, the feasibility and technical success of robotically-assisted PCI for complex coronary lesions were investigated in 334 procedures from 315 patients included in the Complex Robotically Assisted Percutaneous Coronary Intervention (CORA-PCI) study. 2 In 108 procedures of robotically-assisted PCI, technical success was 91.7% and clinical success was 99. 1%.…”
Section: Myocardial Revascularization Percutaneous Coronary Interventmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Glimpsing to the future, the feasibility and technical success of robotically-assisted PCI for complex coronary lesions were investigated in 334 procedures from 315 patients included in the Complex Robotically Assisted Percutaneous Coronary Intervention (CORA-PCI) study. 2 In 108 procedures of robotically-assisted PCI, technical success was 91.7% and clinical success was 99. 1%.…”
Section: Myocardial Revascularization Percutaneous Coronary Interventmentioning
confidence: 99%
“…A propensitymatched analysis of 82 pairs showed that the procedures were longer in patients undergoing robotically-assisted PCI compared with patients undergoing standard PCI, but clinical success rates were similar. 2 Robotically-assisted PCI might find its niche sooner than expected, boosted by the opportunity to further reduce radiation burden to the operator and team.…”
Section: Myocardial Revascularization Percutaneous Coronary Interventmentioning
confidence: 99%
“…Since then several reports have demonstrated the feasibility of robotic PCI for complex procedures including multi‐lesion CAD, allograft vasculopathy, vein graft PCI, unprotected left main (LM) PCI and ST elevation myocardial infarction (STEMI) . The Complex Robotically Assisted (CORA) PCI study reported the safety and feasibility of robotically assisted PCI in clinical practice with a high proportion of complex lesions (Figure ) . In this single center study, all patients undergoing PCI procedures performed by a single operator, either robotically or manually, over an 18‐month period were enrolled.…”
Section: The Systemsmentioning
confidence: 99%
“…Since then several reports have demonstrated the feasibility of robotic PCI for complex procedures including multi-lesion coronary artery disease, allograft vasculopathy, vein graft PCI, unprotected left main PCI, and ST elevation myocardial infarction (STEMI) 28,29. The Complex Robotically Assisted (CORA) PCI study evaluated the safety and feasibility of robotically assisted PCI and compared clinical outcomes against manual PCI in an all-comers, real-world clinical practice 30. This study enrolled 334 patients, with 108 patients (157 lesions) in the robotic group and 226 patients (336 lesions) in the manual group.…”
Section: Corpath 200 and Coronary Interventionsmentioning
confidence: 99%